Concepções sobre beleza de jovens com cegueira congênita - Oliveira, Everton Luiz de (2012)
In a society governed by consumption, the desire for beauty is linked to the concepts of contemporary history; this concept has been transformed into a variety of beauty products for fitness and body available on store shelves, designed to help achieve these standards of beauty; people experience pressure to fit into the social ideals of beauty and they are affected both physically and psychologically; the promotion of these ideologies remains a powerful predictor of consumption patterns of individuals with respect to goods, services and products; the perception of beauty is not only determined by the outcome of genetic or biological processes but is also the privileged access to these resources. This exacerbated concern about physical beauty is evidenced in most physical activities, as they allow for a clear perception of body shape. Given that the learning processes in congenitally blind people are different from those who have visual sensations, there was a concern about that, in a world governed essentially by visual shapes and formulated conceptions, people with blindness could show concepts about beauty, rejecting or accepting the standards / models of beauty historically accepted and validated. Thus, this qualitative and descriptive study was aimed at investigating and understanding the social definition of beauty from the perceptions of people with congenital blindness; and, moreover, this article explains, discusses and examines the effects of these perceptions and evaluations of the other person in terms of physical attributes among individuals related to the social environment, from the own voices of these teenagers. A structured interview was adopted to gather data, which were recorded and transcribed in full and allowed for the qualitative analysis of the entire contents through content analysis. A study was carried out in cooperation with two Regional Boards of Education in the central region of the State of São Paulo and three teenagers with congenital blindness enrolled in high school were selected. The results pointed out the generalized and sublimated way that beauty is seized, internalized and recognized by blind people through the day-to-day practices. Goodness, kindness, gentleness, serenity, respect, courtesy, tenderness, and other moral, social and ethical characteristics were materialized in the beauty, suggesting a positive correlation between beauty and goodness and / or what is good. Voice perception is especially important for blind individuals in allowing them to recognize other people and their aims, and also enable them to evaluate their beauty. Other personal items such as clothing, perfume and personal hygiene practices were also regarded, to a lesser degree, as important items and components to help define beauty. One can find that there is a dissociation between beauty and body, so that the recent (but not so new) phenomenon of the cult of the body, when people make efforts to get in shape and achieve a vigorous, young, toned, symmetrical body, seems not to permeate the senses about ideas, behaviors and perspectives of people with blindness. Finally, language plays important roles in defining body as the image that an individual has of his or her body and other people s bodies, and is likewise used to create symbols, meanings and definitions of beauty, especially in situations where tactile exploration is not possible or allowed, as is the case of another person s body.